Politeness Strategies in Cross-Cultural Communication: A Pragmatic Approach - Puput Handriani; Annisa Putri Dinata; Fauzia Amelia Siregar; Deasy Yunita Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research looks at the part of politeness strategies in cross-cultural communication, concentrating on Asian, European, and African cultures. A qualitative approach was used, and data were gathered through intercultural dialogues and interviews with 30 participants. The results show important cultural differences in using positive and negative politeness strategies. Asian cultures focused on indirectness, honorifics, and non-verbal cues to preserve harmony and hierarchical respect, while European cultures combined directness with mitigation methods like humor and politeness markers. African cultures used inclusive language, storytelling, and indirectness to build group cohesion. This study emphasizes the significance of intercultural competence for handling cultural differences and enhancing communication in various environments.